Morphological and physical characteristic of stone mastic asphalt mixture incorporating nano silica - Putra Jaya, Ramadhansyah; K. A., Masri; Ahmad Kamil, Arshad; Mohd Zul Hanif, Mahmud (Bentham Science Publishers, 2020)
Introduction: Asphalt binder plays an important role in contributing to the good performance of asphalt mixture. However, the interlocking structure of asphalt binder is delicate and sensitive due to surrounding temperature and moisture. Methods: Previously, asphalt binder usually modified with polymer modifier. But, this type of modifier has low temperature susceptibility. To overcome this, nanomaterial is introduced to enhance the performance of virgin asphalt binder. Among the crucial evaluation of nano-modification is to evaluate its microstructural changes through morphological property evaluation. The addition of nanomaterial then will significantly improve the inner structure of asphalt binder and reduce the effect of those problems. Aim: Thus, the aim of this study was to assess the morphological properties of nanosilica modified asphalt binder to determine the inner structured properties of modified specimen. Results: Among the morphological tests conducted for asphalt binder in this study were Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD) and Atomic Force Microscope (AFM). From SEM image analysis and XRD evaluation, the existence of Nanosilica (NS) inside the asphalt binder was well dispersed and from these two tests, the existence of NS inside asphalt binder was verified. From AFM results, most of NS-MB images before and after ageing conditions displayed the typical bee structure (Catana Phase). Conclusion: It was also concluded that the addition of NS in asphalt binder improved its surface stiffness. The overall surface stiffness of the asphalt binder after aging was increased and the surface became more solid.